Efektivitas Penggunaan Media Spinning Wheel dalam Meningkatkan Keterampilan Berpikir Kritis Siswa pada Mata Pelajaran IPA Kelas IV MI Nurul Yaqin Lompo Kabupaten Bone - Herwin, Herwin; Rasyid, Nirwana; Hasan, Hasan (Institut Agama Islam Negeri (IAIN) Bone, 2023)
This research aims to determine the Effectiveness of Using Spinning Wheel Media in Improving Students' Critical Thinking Skills in Class IV Science Subject, MI Nurul Yaqin Lompo, Bone Regency. The type of this research is quantitative. The research design used in this study was a pre-experimental design with a one-group pretest-posttest design. The population is all students of Class IV of MI Nurul Yaqin Lompo, Bone Regency. Researchers took a sample of class IV totaling 22 students. The sampling used in this research is saturated sampling. Data collection techniques using tests, documentation and observation. Data analysis techniques using descriptive data analysis and inferential data analysis.The results of this study indicate that the spinning wheel media is effective in improving students' critical thinking skills. This can be seen by the results of hypothesis testing with decision making. If the significance value (2-tailed) < 0.05 then Hâ‚€ is rejected and Hâ‚ is accepted. If the significance value (2-tailed) > 0.05 then Hâ‚€ is accepted and Hâ‚ is rejected. From the data obtained, it shows a sig.2(tailed) value of .000 <0.05, so it can be said that Hâ‚€ is rejected and Hâ‚ is accepted.